1987
DOI: 10.1111/j.1365-2362.1987.tb02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum cardiac specific troponin‐I with creatine kinase, creatine kinase‐MB isoenzyme, tropomyosin, myoglobin and C‐reactive protein release in marathon runners: cardiac or skeletal muscle trauma?

Abstract: Problems arise in distinguishing skeletal from cardiac muscle trauma on the basis of serum enzyme tests following severe muscle exercise. The contributions of cardiac and skeletal sources have been assessed in eleven marathon runners by measuring pre- and post-race serum levels of cardiac-specific myofibrillar troponin-I together with total creatine kinase, creatine kinase-MB isoenzyme, myoglobin, myofibrillar tropomyosin and C-reactive protein. Total creatine kinase, creatine kinase-MB isoenzyme, tropomyosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(50 citation statements)
references
References 30 publications
(6 reference statements)
5
41
0
4
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29] Cardiac troponin I also remains elevated longer, usually up to 10-14 days.20 Recently it has also been shown that cTnI is an important prognostic indicator in patients presenting with unstable angina, even when CK-MB is not e l e~a t e d . l~\~&~~ Our study supports that notion.…”
Section: Why Use Cardiac Troponin I?mentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29] Cardiac troponin I also remains elevated longer, usually up to 10-14 days.20 Recently it has also been shown that cTnI is an important prognostic indicator in patients presenting with unstable angina, even when CK-MB is not e l e~a t e d . l~\~&~~ Our study supports that notion.…”
Section: Why Use Cardiac Troponin I?mentioning
confidence: 99%
“…[10][11][12][13] Published studies have demonstrated the improved usefulness of cTnl and cTnT for the diagnosis of AMI [14][15][16][17][18] compared with creatine kinase MB, the most frequently used marker of AMI. [19][20][21][22] Increased serum concentrations of cTnl and cTnT have been shown to be more tissue specific for myocardial damage than other cardiac markers. [22][23][24][25] Furthermore, since the majority of cardiac troponins are myofibril bound, their release in serum may correlate with the extent of cardiac necrosis after myocardial infarction, providing a noninvasive method for assessing infarct size.…”
Section: We Studied the Distribution Of Cardiac Troponins I (Ctnl) Anmentioning
confidence: 99%
“…In the late 1980's a first assay (radioimmunoassay, RIA) for specific detection of cTn was made available, and shortly afterwards several more practical assays based on immunoenzymatic techniques were developed (1,2). The clinical adoption of cTn immunoassays was based on the assumption that the specific antibodies used in the assays were able to distinguish cTnI or cTnT from their skeletal muscle isoforms (2), thus enabling to reliably identify a cardiac myocyte injury.…”
mentioning
confidence: 99%